Organic Fertilizer Types at Different Interval Comparison to Butterfly Pea Flower Growth and Yields - Nurjanah, Resti; Kusumiyati; Hamdani, Jajang Sauman (Jurnal Agrinika: Jurnal Agroteknologi dan Agribisnis, 2023)
The butterfly pea (Clictoria ternatea) is one of the horticulture plants. It is part of the ornamental plant group. This plant has many uses, such as food colouring and herbal remedies. Butterfly peas are cultivated organically. However, there needs to be more research regarding adding varieties of organic fertilizers and different fertilization intervals to the plant. The research was executed in Sukalaksana Village, Samarang Subdistrict, Garut Regency, whereas the quality analysis was completed in the Horticulture Cultivation Department of UNPAD Agriculture Faculty. Experimental design of factorial Rancangan Acak Kelompok (RAK) / Randomized Block Design was used. The main factor is the liquid organic fertilizer, made from three different materials: banana stems LOF, chicken manure LOF, and Nasa LOF. The second factor is the fertilization intervals, which were scheduled in three different intervals: once a week, once every two weeks, and once every three weeks. Each interval was repeated three times. Results showed interaction between organic fertilizer types and fertilization intervals on leaf numbers, shoot and roots ratio, number of flowers and flower weight. The best interaction was LOF chicken manure types with fertilization intervals of 3 weeks, which gave higher results in the number of leaves, shoot and root ratio, number of flowers per plant, flower weight per plant and antioxidant content.